The association of IL-10 (-592A/C) gene polymorphism with progression of Type 2 Diabetes Mellitus in Basrah Province-Iraq - Hamid, Saja Majid; Shani, Wafaa Sadoon (Iraqi Journal of Science, 2018)
The study was aimed to investigate the association between IL-10 (-592A/C) gene polymorphism with the progression of type 2 diabeteis mellitus in Basrah Province. This study included (100) subjects (30) person as a control group and (70) patients with T2DM. The patients were distributed as two groups according to Their gender and duration of the disease: group for short duration (≤ 5 years) and group for long duration( >5 years). Lipid profile and glucose concentrations were measured by COBAS analyzer while IL-10 (-592A/C) gene polymorphism was genotyped by using (RFLP-PCR) technique. CC genotype frequency showed a significant decrease while CA genotype revealed significant increase ( p≤0.05) in T2DM compared with controls .No significant differences were observed in the allelic frequencies between both groups. Gender and duration of diabetes didn’t show any significant differences. There is significant association between CA genotype with the risk of T2DM (OR=1.50, 95% CI=1.035-2.173). We concluded that IL-10 (-592A/C) gene polymorphism contribute in development of T2DM.